IMAGING AND TARGETING PROGRAMMED DEATH LIGAND-1 (PD-LI) EXPRESSION (2021)
The presently disclosed subject matter provides compositions, kits, and methods comprising imaging agents that can detect Programmed Cell Death Ligand 1 (PD-L1). The presently disclosed imaging agents can be used to detect diseases and disorders, such as cancer, infection, and inflammation, in a subject.